Clinically important microbial diversity and its antibiotic resistance pattern towards various drugs. Issue 6 (November 2019) - Boovaragamoorthy, Gowri M.; Anbazhagan, Murugadas; Piruthiviraj, Prakash; Pugazhendhi, Arivalagan; Kumar, Smita S.; Al-Dhabi, Naif A.; Mohammed Ghilan, Abdul-K.; Arasu, Mariadhas V.; Kaliannan, Thamaraiselvi
Abstract: Background: Increased use of antibiotics in poultry leads to the development of antimicrobial resistance among the commensal bacterium of broiler chickens. Objective: In this study, we aimed at studying the effect of periodic administration of therapeutic antibiotics against the bacterial diversity in poultry litters collected from broiler chickens. Methods: Poultry litters were collected randomly at regular intervals after administration of antibiotics (1st, 12th and 22nd day) to the chicken. Bedding material without litters served as control. Phenotypic observations showed that there is a difference in the bacterial richness isolated at regular intervals. A total of 32 bacteria were isolated from poultry letters and are grouped into ten different genus. Isolated bacterial species were further confirmed by16S rRNA sequencing. Results: Antibiotic susceptibility profile of isolated bacterial species exhibited strong resistance towards 13 selected antibiotics. These results substantiate that administration of antibiotics leads to the alterations in bacterial diversity and development of antimicrobial resistance among the commensal bacteria of poultry litter. Conclusion: This high selection pressure of therapeutic antibiotics may lead to species selection and development of antibiotic resistance among bacterial population. Development of such species selection may access the human and other organisms via food chain and can cause severe health defects.